Growth Performance of Two Cowpea Varieties with Application of Water Hyacinth Root Extract as Seed Priming - Hikma Ellya; Mimie Rafida; Ronny Mulyawan; Raihani Wahdah; Gani Jawak (SEAS (Sustainable Environment Agricultural Science), 2024)
Nagara cowpea seeds are susceptible to deterioration during storage, thus seed viability performance must be improved with various techniques including seed invigoration. Organic priming is an invigoration technique that can be obtained from several plants that contain growth regulators. Water hyacinth is an aquatic plant in swampy areas that can be used as a raw material for organic priming. This study aims to determine the response and the best concentration of water hyacinth root extract on the growth of two cowpea varieties. This study used a completely randomized design (CRD) split plot with the main factor being cowpea varieties (G) consisting of 2 levels, G1 (Nagara cowpea) and G2 (KT9 cowpea). The subplot factor is water hyacinth root concentration (C) consisting of 4 levels C0 (without priming), C1 2.5%, C2 5.0%, C3 7.5%. The results showed that the application of water hyacinth root extract affected the growth of two cowpea varieties on plant height, number of branches and number of leaves. The highest plant height was in KT9 cowpea soaked with 5% concentration of root extract. The highest number of branches in Nagara cowpea soaked in water hyacinth root extract at concentration 2.5%. The highest number of leaves in cowpea KT9 soaked in water hyacinth root extract at concentration 7.5%.